Doping of Hollow Urchin-like MnO[sub.2] Nanoparticles in Beta-Tricalcium Phosphate Scaffold Promotes Stem Cell Osteogenic Differentiation - Qian, Enze; Eltawila, Ahmed; Kang, Yunqing (International journal of molecular sciences, 2025)
Effective osteogenesis for bone regeneration is still considerably challenging for a porous β-tricalcium phosphate (β-TCP) scaffold to achieve. To overcome this challenge, hollow manganese dioxide (H-MnO[sub.2]) nanoparticles with an urchin-like shell structure were prepared and added in the porous β-TCP scaffold. A template-casting method was used to prepare the porous H-MnO[sub.2]/β-TCP scaffolds. As a control, solid manganese dioxide (S-MnO[sub.2]) nanoparticles were also added into β-TCP scaffolds. Human bone mesenchymal stem cells (hBMSC) were seeded in the porous scaffolds and characterized through cell viability assay and alkaline phosphatase (ALP) assay. Results from in vitro protein loading and releasing experiments showed that H-MnO[sub.2] can load significantly higher proteins and release more proteins compared to S-MnO[sub.2] nanoparticles. When they were doped into β-TCP, MnO[sub.2] nanoparticles did not significantly change the surface wettability and mechanical properties of porous β-TCP scaffolds. In vitro cell viability results showed that MnO[sub.2] nanoparticles promoted cell proliferation in a low dose, but inhibited cell growth when the added concentration went beyond 0.5%. At a range of lower than 0.5%, H-MnO[sub.2] doped β-TCP scaffolds promoted the early osteogenesis of hBMSCs. These results suggested that H-MnO[sub.2] in the porous β-TCP scaffold has promising potential to stimulate osteogenesis. More studies would be performed to demonstrate the other functions of urchin-like H-MnO[sub.2] nanoparticles in the porous β-TCP.